1981
DOI: 10.1021/ja00404a002
|View full text |Cite
|
Sign up to set email alerts
|

Propensity rules for vibration-induced electron detachment of anions

Abstract: 3971using high power pulsed lasers3394 is suitable for more conventional mass spectrometers in which ion-residence times arelod s. ciation of isomers often yields fragment ions in ratios that vary only slightly with the structure of the mecursor ion.z935 ~ -* Thus infrared photodissociation can be developed as a complementary technique to collisional activation for ion structure analysis. In particular, infrared excitation may be better suited to distinguish isomeric species because collision-induced disso-Ack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
139
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(147 citation statements)
references
References 1 publication
8
139
0
Order By: Relevance
“…With regard to the second question, Simons [12] showed that for a slightly unbound state like the present shape resonance two mechanisms may compete. One is via the direct electronic process, which involves a conventional anion-neutral Franck-Condon factor, weighted by how much the wave function of a given mode samples areas of the potential surface with large widths Γ(Q).…”
Section: Pacs Numbersmentioning
confidence: 95%
See 2 more Smart Citations
“…With regard to the second question, Simons [12] showed that for a slightly unbound state like the present shape resonance two mechanisms may compete. One is via the direct electronic process, which involves a conventional anion-neutral Franck-Condon factor, weighted by how much the wave function of a given mode samples areas of the potential surface with large widths Γ(Q).…”
Section: Pacs Numbersmentioning
confidence: 95%
“…One approach to experimental study of autodetachment is based on vibrational photoexcitation of bound anions and detection of autodetached electrons [3][4][5][6][7][8], but the autodetaching anions can also be formed by electron attachment [9,10]. Various aspects of the theory were explained in the work of Simons [2,[11][12][13], with emphasis on vibrational autodetachment that requires inclusion of non-Born-Oppenheimer coupling, the theory of which has initially been inspired by the work on the related process of vibrational autoionization [14].…”
Section: Pacs Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a detachment spectrum was obtained by scanning the laser near the ν 11 vibrational levels and the ν 11 frequency measured for the DBS was found to be identical to that of the neutral phenoxy, as resolved in the PE spectra. Thus, there is a propensity rule of ∆v = −1 for the autodetachment, 151 first derived for autoionization of Rydberg states of H 2 . 152 The allowed and observed autodetachment channels are indicated in Fig.…”
Section: B Resonant Pe Imaging and Spectroscopy Of Cold Phenoxide VImentioning
confidence: 99%
“…Recently, we directly observed mode-specific vibrational autodetachment from DBSs of cold phenoxide anions, 36 which were cooled in a temperature-controlled ion trap to eliminate vibrational hot bands and minimize rotational broadening. The ∆v = −1 vibrational propensity rule, which was initially developed for autoionzation from Rydberg states 37 and extended to autodetachment, 38 was directly observed. More importantly, the vibrational frequencies of the DBS were measured to be the same as the neutral, suggesting the extra electron in the DBS of the anion has very little effect on the neutral core, analogous to a Rydberg state.…”
mentioning
confidence: 99%